2013
DOI: 10.18553/jmcp.2013.19.9.783
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Patient Care Caused by Drug Shortages: A Survey

Abstract: BACKGROUND: Drug shortages pose a serious challenge for health care institutions, often interfering with patient care. A common practice during a drug shortage is to select an alternate therapeutic; however, these agents often present challenges and may create safety concerns. Patient harms including adverse events and medication errors may occur. Patients may also file complaints because of drug shortages. OBJECTIVE: To measure the effect of drug shortages on patient outcomes, clinical pharmacy operations, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 8 publications
2
110
0
4
Order By: Relevance
“…Our survey findings regarding FTE results are similar to those found in other surveys. 31 Several examples of our systematic process and action steps to addresses drug shortages are included in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey findings regarding FTE results are similar to those found in other surveys. 31 Several examples of our systematic process and action steps to addresses drug shortages are included in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Medicines shortages (also referred to as drug shortages) are a challenging global phenomenon affecting all hospital and health systems [1][2][3][4][5]. Furthermore it is a phenomenon that if left alone threatens to become a crisis in terms of delivering patient care [6,7].…”
Section: A Global Phenomenonmentioning
confidence: 99%
“…Not only, but mainly in oncology, specific products are needed for on-going multicycle therapies according to international protocols. Disruption and switch to an alternative is rarely feasible and com-promises seriously patient safety and clinical outcome [1,8,9].…”
Section: A Global Phenomenonmentioning
confidence: 99%
“…22 Drug shortages have become common among many classes of medication, but the number of antimicrobials impacted by drug shortages poses a serious problem for the provision of anti-infective therapy in the United States. 23,24 A recent survey of pharmacy directors by McLaughlin et al (2013) sought to measure the impact of drug shortages on patient outcomes, clinical pharmacy operations, patient complaints, and institutional cost. 25 The authors found that 85.3% of respondents reported the use of alternative medications; 70.8% reported delays in medication therapy; and almost 50% reported a need for increased patient monitoring.…”
Section: Impact Of An Intravenous Trimethoprim/sulfamethoxazole Shortmentioning
confidence: 99%